Forehand Lob Technique Model in Badminton Using Drill (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
Badminton is a popular sport in Indonesia for children to adults. This can be seen from many people in cities and villages who play badminton both in indoor and outdoor courts. The purpose of this study was to develop the basic techniques of forehand lob in badminton using the drill. The research method was research and development using Borg and Gall models. The process of collecting data used documents, questionnaires, observation and tests. Model analysis techniques used (1) trial in small and large groups; and (2) judgment expert. The results show that there are two types of net used in the development of the model namely standard net and multilevel net. Each type of exercise consists of 6 models which are model L, V, U, N, W, and M. Each level has three categories, namely easy, medium, and difficult.